1999
DOI: 10.1006/gyno.1999.5487
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Brachytherapy for Vaginal Recurrences of Endometrial Carcinoma

Abstract: Objective. The aim of this study was to evaluate the efficacy of interstitial brachytherapy in the management of vaginal recurrences of endometrial carcinoma.Methods. Thirty patients received interstitial irradiation, with or without external beam radiotherapy. They were followed for a minimum of 5 years or until death.Results. The median age was 66 years at initial diagnosis of endometrial cancer. FIGO stages included Stage I (n ‫؍‬ 18), Stage II (n ‫؍‬ 7), and Stage III (n ‫؍‬ 5). All patients were treated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 30 publications
1
16
1
2
Order By: Relevance
“…In our series all stage III tumors were large tumors (≥ 5 cm) what also could explain the bad outcome of these patients. Time to relapse was a significant prognostic factor in our series and in series concerning surgical treatment but not in other series concerning radiotherapy [5,22,43]. Both in our series and in the series of Ito et al no significant differences were found between brachytherapy alone and combined brachytherapy and EBT, while Virostek et al reported treatment modality and total dose as prognostic factors [22,44].…”
Section: Authors Patients Brachy-brachytherapy Brachy-ebtcontrasting
confidence: 60%
See 4 more Smart Citations
“…In our series all stage III tumors were large tumors (≥ 5 cm) what also could explain the bad outcome of these patients. Time to relapse was a significant prognostic factor in our series and in series concerning surgical treatment but not in other series concerning radiotherapy [5,22,43]. Both in our series and in the series of Ito et al no significant differences were found between brachytherapy alone and combined brachytherapy and EBT, while Virostek et al reported treatment modality and total dose as prognostic factors [22,44].…”
Section: Authors Patients Brachy-brachytherapy Brachy-ebtcontrasting
confidence: 60%
“…The use of fluoroscopy or CT-assisted guidance or open MRI necessitates more expensive infrastructure while laparotomy-or laparoscopy-aided implantation of brachytherapy tubes requires intensive cooperation with surgeons [7,8,33,40,43].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations